Peran Strategi Bisnis Dalam Meningkatkan Keunggulan Bersaing di Industri Fashion - Linda Maryani; Harmon Chaniago (Jurnal Riset Bisnis dan Investasi, 2019)
This research aims to analyze the influence of business strategy in increasing competitive advantage. Selected population is the Creative Industry SMEs in the fashion sector in Bandung, amounting to 507 population in the period 2010-2017 and the number of samples of 223 SMEs fashion business in Bandung. Data collection using questionnaires with Likert scale. Data analysis using Regression Linear with SPSS 22.0. The result of data analysis shows that the research model can be accepted with goodness of fit test, that is effect positive and significant to competitive advantage.